BOND STRENGTH OF THE UNRESIN CONTINUOUS CARBON FIBER CABLES - Djamaluddin, Rudy (Jurnal Ilmiah Desain & Konstruksi, 2008)
Unresin continuous carbon fibers, UCCF, is a new material developed as an alternativereinforcement and cable sling for civil construction. Generally, UCCF has the tensilestrength of 4800 Mpa with Modulus Elasticity of 230 Gpa. This material is also has verygood characteristic of stainless. Integrated carbon fiber will become a cable sling whichused as a reinforcement in reinforced concrete and as a tendon in prestress concrete. As areinforcement, the tensile strength in reinforced concrete would be a main parameter tobe identified in the research by doing tensile test. Research shows that the tensile strengthof this fiber is lower than reinforcing steel relatively. With this research, it shows alsothat the tensile strength is influenced by diameter of fiber.